1997
DOI: 10.1111/j.1600-0684.1997.tb00046.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction of the owl monkey (Aotus spp.) in captivity

Abstract: The reproduction performance of captive owl monkeys, a breed used extensively in biomedical research, was observed at the Battelle Primate Facility (BPF). The colony grew through captive breeding, imports from the Peruvian Primatological Project, and others to a peak size of 730. It included seven karyotypes of Aotus sp. Results showed that owl monkeys can breed successfully in a laboratory in numbers sufficient to sustain modest research programs. Reproductive success increases when pairs are compatible, of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…As for the gestation length in owl monkeys, there are variations of 120–140 days [7, 18] and of 149–159 days [8]. Hall and Hodgen [10] suggest that, based on the early identification of chorionic gonadotropin, the gestational length may be of 126 days.…”
Section: Discussionmentioning
confidence: 99%
“…As for the gestation length in owl monkeys, there are variations of 120–140 days [7, 18] and of 149–159 days [8]. Hall and Hodgen [10] suggest that, based on the early identification of chorionic gonadotropin, the gestational length may be of 126 days.…”
Section: Discussionmentioning
confidence: 99%
“…Malaga et al (1997) reported a diminishing interbirth interval in multiparous pairs with 11 months between the first and second births, 9.9 months until the third birth, and 8.8 months between subsequent parturitions. The mean time from pairing to first parturition was 14.6 ± 7.7 months (Malaga et al, 1997). The mean time from pairing to first parturition was 14.6 ± 7.7 months (Malaga et al, 1997).…”
Section: Reproductionmentioning
confidence: 99%
“…Corticotropin-releasing hormore (CRH) peaks during mid-gestation, at days 60-80 in owl monkeys (Power et al, 2010). Malaga et al (1997) reported a diminishing interbirth interval in multiparous pairs with 11 months between the first and second births, 9.9 months until the third birth, and 8.8 months between subsequent parturitions. Malaga et al (1997) reported a diminishing interbirth interval in multiparous pairs with 11 months between the first and second births, 9.9 months until the third birth, and 8.8 months between subsequent parturitions.…”
Section: Reproductionmentioning
confidence: 99%
“…This is a complex genus with many species defined by 11 divergent karyotypes representing at least 10 different species (72,99). Because there are only 2 phenotypes (rednecked and gray-necked), karyotyping is essential for setting up breeding colonies (76). Some karyotypes have specific disease problems such has hypereosinophilia in Karyotype VI (3).…”
Section: The New World Monkeysmentioning
confidence: 99%